A short measure of general policy alienation: Scale development using a 10‐step procedure. (29th March 2017) - van Engen, Nadine A.M.
Abstract : Public administration research is becoming increasingly quantitative. As seen in psychological and managerial research, the result is a growing demand for valid and reliable measures. Given the tradition of contextually embedded research in public administration – where research should cover multiple factors to find useful answers to real‐life problems – survey research should ideally incorporate many measures. This is driving a need for short measures that do not compromise on validity and reliability. In this study, a short measure of general policy alienation is developed and tested, observing stringent criteria. The analyses on three independent datasets (N = 1, 183, N = 354, and N = 933) show that the original multidimensional 26‐item measure can be abbreviated to a short five‐item measure with limited compromises on validity and reliability. Practical applications and methodological implications regarding both the developed measure and the 10‐step procedure used are discussed.